Sense dalam Buku Puisi Ada Berita Apa Hari Ini, Den Sastro? (Perspektif Hermeneutika Paul Ricoeur) - Nurfaika, Nurfaika; Nensilianti, Nensilianti; Saguni, Suarni Syam (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research aims to analyze the meaning of sense in the poetry book Ada Berita Apa Hari, Den Sastro? by Sapardi Djoko Damono which is studied using Paul Ricoeur's hermeneutic theory. This research is descriptive qualitative. The results of this study are, The first poem describes a sense of loneliness, the second poem describes two people who are disappointed and then decide to end their relationship. The next poem means someone who tries to survive the trials of life. Next, it describes the feeling of guessing about something. The next poem means that everything has been destined according to its own portion and also means to rise from suffering. The results of the interpretation of the meaning of sense contain many meanings of life that occur in society, namely a sense of loneliness, disappointment, regret, strength to undergo life trials and suffering.